2010
DOI: 10.1016/j.jaac.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Classification of Eating Disorders in Children and Adolescents: How Does DSM-IV-TR Compare to Empirically-Derived Categories?

Abstract: Objective-The purpose of this study was to empirically derive eating disorder phenotypes in a clinical sample of children and adolescents using latent profile analysis (LPA) and compare these latent profile (LP) groups to the DSM-IV-TR eating disorder categories.Method-Eating disorder symptom data collected from 401 youth (ages 7-19; mean 15.14 ± 2.35y) seeking eating disorder treatment were included in LPA; general linear models were used to compare LP groups to DSM-IV-TR eating disorder categories on pre-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 41 publications
2
33
0
3
Order By: Relevance
“…6 On the basis of the criteria from the fourth edition of the DSM, most adolescents were diagnosed with EDs not otherwise specified (EDNOS), a group of heterogeneous disorders composed primarily of subthreshold AN or BN. 13 The estimated lifetime prevalence of EDNOS in adolescents is 4.8%. 14 Rates of medical complications in EDNOS are similar to full-threshold disorders.…”
Section: Epidemiologymentioning
confidence: 99%
“…6 On the basis of the criteria from the fourth edition of the DSM, most adolescents were diagnosed with EDs not otherwise specified (EDNOS), a group of heterogeneous disorders composed primarily of subthreshold AN or BN. 13 The estimated lifetime prevalence of EDNOS in adolescents is 4.8%. 14 Rates of medical complications in EDNOS are similar to full-threshold disorders.…”
Section: Epidemiologymentioning
confidence: 99%
“…At least half of the patients seen at eating disorder treatment centres are diagnosed with an EDNOS (Eddy et al, 2010;Fairburn & Bohn, 2005), and individuals with EDNOS present similarly to those with AN and BN in terms of symptom severity and impairments in functioning (Turner & Bryant-Waugh, 2004). Past systematic reviews have tended to exclude EDNOS groups due to the heterogeneity of this diagnostic category (e.g., Van den Eynde et al, 2011), but this results in a large proportion of eating disorder cases being omitted from research.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified subgroups of individuals resembling those with BN that are characterized by binge-eating and purging symptoms in both clinical and community populations by using latent class analysis (LCA) [30][31][32][33][34][35][36][37] or latent profile analysis (LPA) [38][39][40][41][42][43][44][45]. Latent class analysis seeks to identify the smallest number of identifiable latent classes (i.e., categories of a latent factor) that account for the association between three or more observed dichotomous and polychotomous variables [46,47].…”
Section: Introductionmentioning
confidence: 99%